2019
DOI: 10.1021/acs.orglett.9b00817
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne–Alkyne Photo-cross-linking on the Flipping-out Field

Abstract: The base flip-inducing nucleic acids are expected to create a specific field for various chemical reactions. We now report a novel type of base-flip-inducing oligodeoxynucleotide and photo-cross-linking reaction. Two 3-arylethynyl-5-methyl-2-pyridone nucleosides, Ph and An, were synthesized, and their properties were investigated. The alkyne–alkyne photo-cross-linking rapidly proceeded by taking advantage of the base-flipping-out field where two alkynes overlap each other. This photo-cross-linking would be a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…Apart from advances in [2 + 2] photocycloaddition, other types of visible light photocross-linking methods have recently been designed. One of the representative works was performed by Onizuka et al This group developed alkyne-alkyne photo-cross-linking based on base-flipping [64] to induce the flipping-out structure of oligonucleotides, 3arylethynyl-5-methyl-2-pyridone nucleosides, which contain a phenyl (19) or an anthracenyl moiety (20) (Figure 11). In the base flipping-out field, two alkynes overlap with each other, and the [2 + 2 + 2] cycloaddition reaction proceed with the alkynes and molecular oxygen to form a 1,4-enedione structure through the single electron transfer (SET) mechanism.…”
Section: Other Photo-cross-linking Methodsmentioning
confidence: 99%
“…Apart from advances in [2 + 2] photocycloaddition, other types of visible light photocross-linking methods have recently been designed. One of the representative works was performed by Onizuka et al This group developed alkyne-alkyne photo-cross-linking based on base-flipping [64] to induce the flipping-out structure of oligonucleotides, 3arylethynyl-5-methyl-2-pyridone nucleosides, which contain a phenyl (19) or an anthracenyl moiety (20) (Figure 11). In the base flipping-out field, two alkynes overlap with each other, and the [2 + 2 + 2] cycloaddition reaction proceed with the alkynes and molecular oxygen to form a 1,4-enedione structure through the single electron transfer (SET) mechanism.…”
Section: Other Photo-cross-linking Methodsmentioning
confidence: 99%
“…9). 65 In this case, efficient alkyne-alkyne photocrosslinking was realized using the heterocombination of Ph(alkyne) and An (alkyne) rather than a homocombination, such as Ph-Ph and An-An. The difference in the reaction rates between the hetero and homocombinations occurred because single electron transfer (SET) is essential for alkyne-type reactions, i.e., SET occurs more readily for the heterocombinations than for the homocombinations because of the difference in redox potential.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…9 Postulated reaction mechanism of alkyne-alkyne photocrosslinking on the flipping-out and base-stacked field. 65 Organic & Biomolecular Chemistry Review…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…For example, RNA editing enzymes flip the target base out of the helix, take the base into an active site, and convert adenine and cytosine to inosine and uracil by accelerating the hydrolysis of the amino group of adenine and cytosine (Figure A). Similarly, artificial oligodeoxynucleotides (ODNs) can also induce the base flipping (Figure B,C) and a specific chemical reaction. Sugimoto’s group previously developed phenylcarbamoyl-modified dA-containing ODNs with the ability of base flipping and found that the base flipping accelerated the RNA-cleaving reaction (Figure D). In our previous study, as base-flipping-inducing artificial bases, , we developed 5-methylpyridone derivatives linked to an aromatic compound with a rigid alkyne linker at the C3 position (Figure B,C). In addition, an efficient alkyne–alkyne photo-cross-linking was realized by taking advantage of the formed flipping-out field …”
Section: Introductionmentioning
confidence: 99%
“…Sugimoto’s group previously developed phenylcarbamoyl-modified dA-containing ODNs with the ability of base flipping and found that the base flipping accelerated the RNA-cleaving reaction (Figure D). In our previous study, as base-flipping-inducing artificial bases, , we developed 5-methylpyridone derivatives linked to an aromatic compound with a rigid alkyne linker at the C3 position (Figure B,C). In addition, an efficient alkyne–alkyne photo-cross-linking was realized by taking advantage of the formed flipping-out field …”
Section: Introductionmentioning
confidence: 99%